(untitled) (Psychology Travelogs, 2024)
The article highlights the issues related to the subjectness of team specialists who provide psychological and pedagogical support to a child with special educational needs. The general content of the concept of subjectness in some interdisciplinary studies is analyzed. The peculiarities of the subjectness of the support specialist are determined, taking into account the content of their professional activity. The author’s approach to understanding the structure of the subjectness of a support specialist is proposed. Based on the theoretical analysis, the components of subjectness of specialists who provide psychological and pedagogical support to a child with special educational needs are identified, including: internal locus of control, reflexivity, self-organization, self-determination in activity and self-efficacy. The results of an empirical study of the degree of formation and peculiarities of manifestation of the proposed components of the subjectness of support specialists are presented. It is established that the degree of formation of the outlined components of subjectness is within the average level. An assumption is made about the tendency to situational subjectness as a complex formation of professional activity of support specialists (depending on the specifics of the professional situation). The necessity of developing a system of psychological measures to optimize the subjectivity of support team specialists is emphasized, taking into account the established patterns of manifestation of individual components of subjectivity in this study.